2006
DOI: 10.1093/annonc/mdj121
|View full text |Cite
|
Sign up to set email alerts
|

Survivin expression in breast cancer predicts clinical outcome and is associated with HER2, VEGF, urokinase plasminogen activator and PAI-1

Abstract: The independent prognostic relevance of survivin, when combined with previous data from model systems implicating survivin in the inhibition of apoptosis, suggests that survivin may be a suitable target for future therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
6
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 40 publications
9
98
6
2
Order By: Relevance
“…Span et al (2004) found similar relationships between survivin, grade III and lack of ER. A recent report in which enzyme-linked immunosorbent assay was used to measure survivin found high levels to relate to poorer outcome, which was independent of other factors (Ryan et al, 2006). However, two immunohistochemical studies report different findings to the present one.…”
Section: Discussioncontrasting
confidence: 62%
“…Span et al (2004) found similar relationships between survivin, grade III and lack of ER. A recent report in which enzyme-linked immunosorbent assay was used to measure survivin found high levels to relate to poorer outcome, which was independent of other factors (Ryan et al, 2006). However, two immunohistochemical studies report different findings to the present one.…”
Section: Discussioncontrasting
confidence: 62%
“…Recently many had showed survivin could be a biomarker of tumor (Waligórska-Stachura et al, 2012;Fraunholz et al, 2012). Ryan et al have found that increased survivin in breast cancer tissue indicating worse treatment response and prognosis (Ryan et al, 2006). Another report showed the elevated survivin in the bronchial aspirates could be the marker of lung cancer (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in XIAP protein levels that we see after treatment of cells with trastuzumab may be in part due to a cellular stress response increasing translation of XIAP from the internal ribosomal entry sequence, although this needs to be tested in our experimental model. Similar to XIAP, the role of another key IAP/BIRC member, survivin, has been identified as a potential prognostic marker in breast cancer (48). An inverse correlation of survivin expression and sensitivity to lapatinib and trastuzumab has been observed in non-IBC ErbB2-overexpressing BT474 and SKBR3 cells, respectively (25,29).…”
Section: Discussionmentioning
confidence: 99%